Human-Centred Artificial Intelligence-Supported Critical Film Literacy Model for SDG 4.7: A Postcolonial Study of Indonesian Cinema - Frikho Fernando Polii; Suyatno Suyatno; Darni Darni (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: The study develops a human-centred model of artificial-intelligence-supported critical film literacy for language education and Sustainable Development Goal (SDG) 4.7. It examines how Indonesian biographical cinema constructs critical awareness and how those constructions can organise responsible AI-supported learning. Method: A qualitative interpretative-critical reanalysis examined Guru Bangsa: Tjokroaminoto, Kartini, and Sultan Agung: Tahta, Perjuangan, dan Cinta. Verbal, visual, narrative, auditory, and cultural signs were analysed through Peircean semiotics, Freirean critical pedagogy, and Bhabha's postcolonial concepts. Abductive cross-film coding organised the evidence into cognitive, affective, and praxis-oriented dimensions and guided pedagogical model derivation. Results: The films construct structural awareness through education, letters, books, public speech, cultural memory, and symbolic spaces; ethical engagement through confinement, exploitation, grief, and responsibility; and transformative agency through organisation, emancipatory literacy, negotiation, leadership, and cultural transmission. These patterns support a six-stage cycle: human first reading, AI-generated alternative interpretation, evidence verification, cultural-bias audit, dialogic synthesis, and independent ethical language production. Novelty: The study integrates critical film literacy, language learning, AI literacy, postcolonial interpretation, and SDGs-oriented education in one operational didactic-semiotic model. Human judgement functions as the organising principle of AI use, while SDG 4.7 provides the central educational purpose and SDGs 5 and 16 provide linked contribution pathways.